Ingredients : the strange chemistry of what we put in us and on us - Zaidan, George (Dutton, 2020)
"Cheese puffs. Coffee. Sunscreen. Vapes. George Zaidan reveals what will kill you, what won't, and why-explained with high-octane hilarity, hysterical hijinks, and other things that don't begin with the letter H. Ingredients offers the perspective of a chemist on the stuff we eat, drink, inhale, and smear on ourselves. Apart from the burning question of whether you should eat that Cheeto, Zaidan explores a range of topics"--